Equações polinomiais: da equação de 1º grau à teoria de Galois - Oliveira, Daniell Ferreira de (2017)
This paper aims to improve the understanding of Mathematics teachers regarding the solution of polynomial equations by means of radicals, focusing on the theory of Galois. The reader _nd in this document a little of Galois's life story, radical resolutions of degree n 4 equations, group, ring and body theories, as well as Galois Theory.